Psychosocial and auditory factors that influence successful music-based auditory training in pediatric cochlear implant recipients - Gfeller, Kate; Mallalieu, Ruth (Frontiers in Human Neuroscience, 2023)
Cochlear implants (CIs), which are designed to support spoken communication of persons with severe to profound hearing loss, can provide improved hearing capability through passive exposure. However, auditory training may optimize perception of spectrally complex sounds such as music or speech. Reviews of music-based training for pediatric CI users have reported modest though variable benefits, as well as problems with attrition. It is presumed that more substantial changes may result from longer, more intensive training; however, the development of protocols sufficiently motivating for sustained intensity is challenging. This article examined the experiences of star pediatric CI users, whose years of music training have yielded exceptional auditory benefits. Greater understanding of their experiences and attitudes may suggest best practices for music-based training. Research aims included: (a) characterizing the musical behaviors and perceptual learning processes of music-centric 1 pediatric CI users, and (b) identifying psychosocial and auditory factors that motivated persistence in auditory training. Methods: We used qualitative and patient-engaged research methodologies, gathering data through questionnaires with open-ended questions. The participants, six music-centric CI users and five parents, described their experiences and attitudes regarding music training, and factors that supported or undermined those experiences. Data were analyzed using reflexive thematic analysis.The codes were consolidated into five themes and organized into a Model of Music-Based Learning for Pediatric Cochlear Implant Recipients. Sustained participation in music training was perceived as a dynamic process including varied musical stimuli, and moderated by intrinsic (attitude, perceived behavioral control) and extrinsic (parents, teachers, peers) influences, hearing status, sound access and background factors. Discussion: These themes highlighted motivational factors that pediatric CI users and parents considered important to sustained, intensive and successful music learning throughout childhood and adolescence. These factors should be considered in the development of music-based training for pediatric CI recipients.